Edukasi dan Penyuluhan Hukum Waris Islam di Desa Lise, Kecamatan Panca Lautang, Kabupaten Sidrap: Education and Counseling on Islamic Heritage Law in Lise Village, Panca Lautang District, Sidrap Regency - Achmad, Achmad; Irwan, Muhammad; Amaliyah, Amaliyah; Muchsin, Putri Rofifah Nabilah; Alam, Andi Rifdah Auliyah; Dany, Ahmad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Inheritance law counseling in Lise Village, Sidenreng Rappang Regency, is a strategic effort to increase public understanding of Islamic inheritance law, which has been largely unknown, especially among vulnerable groups. This activity is carried out through a participatory approach, including focus group discussions and real case studies, which make it easier for participants to digest the material and apply it in their daily lives. The Hasanuddin University Faculty of Law team plays an active role in assisting the community, providing legal education, and making information related to legal aid services accessible. The results of the counseling indicate an increase in public awareness of managing inheritance rights in a fair and legally compliant manner, which can simultaneously minimize the potential for inheritance conflicts in the village environment. This counseling is not only a means of knowledge transfer, but also an effort to empower the law for the community oriented towards social justice and legal certainty. The success of this activity opens up opportunities to strengthen the network of cooperation between the community, village officials, and legal aid institutions in supporting law enforcement in accordance with local and religious values. Thus, inheritance law counseling in Lise Village is a clear example of the contribution of legal education in building a more empowered and harmonious society.